Knowledge and application of biosecurity protocols in health professionals during the COVID-19 - Boroneo-Cantalicio, Mariela (2022)
Objective. To determine the relationship between knowledge and application of biosafety protocols by COVID-19. Methods. The research was descriptive, correlational and cross-sectional. The population consisted of 45 health workers belonging to the Hospital Materno Infantil Carlos Showing Ferrari de Huánuco, 2020, who responded to a knowledge questionnaire and an observation guide on biosafety by COVID-19. Spearman's rho correlation coefficient was used for statistical analysis. Results. 97.8 % of the workers (44) showed correct compliance with biosafety protocols by COVID-19 and 62.2 % (28 workers) achieved regular level knowledge. On the other hand, knowledge was significantly associated with compliance with biosafety protocols by COVID-19, with p = 0.000; likewise, this application of protocols is significantly related to the knowledge dimensions: knowledge of the disease (p = 0.000), knowledge of biosafety (p = 0.000), knowledge of universality (p = 0.000), knowledge of barrier use (p = 0.020) and knowledge of means of disposal (p = 0.006). Conclusions. Knowledge is significantly related to the application of biosafety protocols by COVID-19.